HUBUNGAN PAPARAN ASAP ROKOK DENGAN KEJADIAN KANKER PAYUDARA PADA USIA MUDA - Ambarita, Winona Vida Vita Nathania; Budiwinata, Winardi; Oktaviyanti, Ika Kustiyah; Priyono, Sasongko Hadi; Rosida, Lena (Homeostasis, 2024)
Abstract: Breast cancer is often discovered and diagnosed at a young age which is associated with family history, gene mutations, and poor lifestyle. One of the risk factors is exposure to cigarette smoke. The aim of the research is to determine whether there is a relationship between exposure to cigarette smoke and the incidence of breast cancer at a young age at Ulin Regional Hospital, Banjarmasin. Analytic observational research method, cross sectional research design. Total sampling of breast cancer patients who seek treatment at the Oncology Surgery Polyclinic of Ulin Banjarmasin Hospital for the period January 2020-November 2023 according to the inclusion and exclusion criteria. Data collection using questionnaires related to cigarette smoke exposure. Analysis using the Fisher test. The results were young breast cancer respondents exposed to cigarette smoke (91.1%), very young age exposed to cigarette smoke (8.9%), young age not exposed to cigarette smoke (40.0%) and very young age not exposed to cigarette smoke (60.0%) with a p-value = 0.016. In conclusion, there is a significant relationship between exposure to cigarette smoke and the incidence of breast cancer at a young age. Keywords: breast cancer, young age, cigarette smoke exposure Abstrak: Kanker payudara sering ditemukan dan didiagnosa pada usia muda yang dikaitkan dengan riwayat keluarga, mutasi gen, serta gaya hidup yang buruk. Salah satu faktor risiko yaitu terpapar asap rokok. Tujuan penelitian mengetahui apakah terdapat hubungan paparan asap rokok dengan kejadian kanker payudara pada usia muda di RSUD Ulin Banjarmasin. Metode penelitian observasional analitik, desain penelitian cross sectional. Pengambilan sampel total sampling pasien kanker payudara yang berobat ke Poliklinik Bedah Onkologi RSUD Ulin Banjarmasin periode Januari 2020-November 2023 sesuai kriteria inklusi dan ekslusi. Pengambilan data menggunakan kuesioner terkait paparan asap rokok. Analisis menggunakan uji Fisher. Hasilnya responden kanker payudara usia muda yang terpapar asap rokok (91,1%), usia sangat muda yang terpapar asap rokok (8,9%), usia muda yang tidak terpapar asap rokok (40,0%) dan usia sangat muda yang tidak terpapar asap rokok (60,0%) dengan p-value = 0,016. Kesimpulannya terdapat hubungan bermakna antara paparan asap rokok dengan kejadian kanker payudara pada usia muda. Kata-kata kunci: kanker payudara, usia muda, paparan asap rokok.